The Application of FTIR Spectroscopy and Chemometrics for the Authentication Analysis of Horse Milk - Arifah, Mitsalina Fildzah; Irnawati, Irnawati; Ruslin, Ruslin; Nisa, Khoirun; Windarsih, Anjar; Rohman, Abdul (Hindawi Limited, 2022)
Expensive milk such as horse’s milk (HM) may be the target of adulteration by other milk such as goat’s milk (GM) and cow’s milk (CM). FTIR spectroscopy in combination with chemometrics of linear discriminant analysis (LDA) and multivariate calibrations of partial least square regression (PLSR) and principal component regression (PCR) was used for authentication of HM from GM and CM. Milk was directly subjected to attenuated total reflectance (ATR) spectral measurement at midinfrared regions (4000-650 cm-1). Results showed that LDA could make clear discrimination between HM and HM adulterated with CM and GM without any misclassification observed. PLSR using 2nd derivative spectra at 3200-2800 and 1300-1000 cm-1 provided the best model for the relationship between actual values of GM and FTIR predicted values than PCR. At this condition, R2 values for calibration and validation models obtained were 0.9995 and 0.9612 with RMSEC and RMSEP values of 0.0093 and 0.0794. PLSR using normal FTIR spectra at 3800-3000 and 1500-1000 cm-1 offered R2 for the relationship between actual values of CM and FTIR predicted values of >0.99 in calibration and validation models with low errors of RMSEC of 0.0164 and RMSEP of 0.0336 during authentication of HM from CM. Therefore, FTIR spectroscopy in combination with LDA and PLSR is an effective method for authentication of HM from GM and CM. Copyright © 2022 Mitsalina Fildzah Arifah et al.